Fundamental pseudo BCK-algebras - Habib Harizavi; Rajab Ali Borzooei; Taiybeh Koochakpoor (Journal of Hyperstructures, 2016)
In this paper, we de ne the relations and on hyper pseudo BCK-algebras and investigate some related properties. We give a necessary and sucient condition for to be regular. By using, we make the quotient hyper pseudo BCK-algebra. Finally, by applying the concept of fundamental on pseudo BCK-algebra, we prove that any pseudo BCK-algebra is fundamental.